Automated Chemical Equation Balancing Using the Apriori Algorithm - Mohialden, Yasmin Makki; Hussien, Nadia Mahmood; Al-Rada, Walaa A Abd (Journal La Multiapp, 2023)
Chemical equations must be balanced to maintain mass conservation. Traditional chemists employed manual processes with meticulous investigation and trial-and-error iterations. Automating and enhancing this difficult process is becoming more popular as machine learning (ML) progresses. We provide a novel Apriori algorithm-based chemical equation balancing method in this paper. Our solution uses the Apriori algorithm to find common itemsets of balanced reactions and translates unbalanced equations into machine-readable language. After that, it reconstructs balanced equations, automating a tedious task.